Brainstem dose is associated with patient-reported acute fatigue in head and neck cancer radiation therapy. Issue 1 (January 2018) - Ferris, Matthew J.; Zhong, Jim; Switchenko, Jeffrey M.; Higgins, Kristin A.; Cassidy, Richard J.; McDonald, Mark W.; Eaton, Bree R.; Patel, Kirtesh R.; Steuer, Conor E.; Baddour, H. Michael; Miller, Andrew H.; Bruner, Deborah W.; et al.
Abstract: Background and purpose: Radiation (RT) dose to the central nervous system (CNS) has been implicated as a contributor to treatment-related fatigue in head and neck cancer (HNC) patients undergoing radiation therapy (RT). This study evaluates the association of RT dose to CNS structures with patient-reported (PRO) fatigue scores in a population of HNC patients. Materials and methods: At pre-RT (baseline), 6th week of RT, and 1-month post-RT time points, Multidimensional Fatigue Inventory (MFI-20) scores were prospectively obtained from 124 patients undergoing definitive treatment for HNC. Medulla, pons, midbrain, total brainstem, cerebellum, posterior fossa, and pituitary dosimetry were evaluated using summary statistics and dose–volume histograms, and associations with MFI-20 scores were analyzed. Results: Maximum dose (Dmax) to the brainstem and medulla was significantly associated with MFI-20 scores at 6th week of RT and 1-month post-RT time points, after controlling for baseline scores ( p  < 0.05). Each 1 Gy increase in medulla Dmax resulted in an increase in total MFI-20 score over baseline of 0.30 ( p  = 0.026), and 0.25 ( p  = 0.037), at the 6th week of RT and 1-month post-RT, respectively. Each 1 Gy increase in brainstem Dmax resulted in an increase in total MFI-20 score over baseline of 0.30 ( p  = 0.027), and 0.25 ( p  = 0.037) at the 6th week of RT, 1-month post-RT, respectively. Statistically significant associations were not found between dosimetry for the other CNS structures and MFI-20 scores. Conclusions: In this analysis of PRO fatigue scores from a population of patients undergoing definitive RT for HNC, maximum dose to the brainstem and medulla was associated with a significantly increased risk of acute patient fatigue.